The assessment of marrow adiposity in type 1 diabetic rabbits through magnetic resonance spectroscopy is linked to bone resorption - Li, Wei; Wang, Wei; Zhang, Minlan; Chen, Qi; Li, Fengyi; Li, Shaojun (Frontiers in Endocrinology, 2025)
BackgroundEnhanced marrow adiposity is frequently linked with a decline in bone density. The underlying mechanisms responsible for bone loss in diabetes are not well understood. In this investigation, we employed an alloxan-induced diabetes rabbit model to unravel the association between marrow fat content and bone resorption, utilizing magnetic resonance spectroscopy.MethodsForty 4-month-old male New Zealand rabbits were randomly allocated into two groups: a control group and an alloxan-induced diabetic group, each consisting of 20 rabbits. Biochemical analyses covered plasma glucose, enzyme levels, lipid profiles, blood urea nitrogen, creatinine levels, and markers of bone turnover. Quantification of bone marrow adipose tissue utilized both MR spectroscopy and histological examinations. Dual-energy X-ray absorptiometry and microcomputed tomography were employed to determine bone density and trabecular bone microarchitectures. The expression levels of marrow adipocyte markers (peroxisome proliferator-activated receptor-gamma2, CCAAT/enhancer-binding protein-α, and fatty acid binding protein 4) and markers of bone resorption [tartrate-resistant acid phosphatase (TRACP) and cathepsin K] were assessed using RT-PCR.ResultsDiabetic rabbits exhibited significant increases in marrow fat fraction (MFF) over time (MFF increased by 13.2% at 1.5 months and 24.9% at 3 months relative to baseline conditions, respectively). These changes were accompanied by the deterioration of trabecular microarchitectures. Marrow adipogenesis was evident through a 31.0% increase in adipocyte size, a 60.0% rise in adipocyte number, a 103.3% increase in the percentage of adipocyte area, and elevated mRNA expressions of marrow adipocyte markers. Osteoclast markers (TRACP and cathepsin K RNA and serum TRACP5b levels) were elevated in diabetic rabbits. MFF exhibited a robust correlation with trabecular bone microarchitectures. A significant positive correlation was identified between ΔMFF and serum ΔTRACP5b levels. Moreover, MFF at 3 months showed a strong positive correlation with serum TRACP5b levels (r = 0.763), as well as with the mRNA expression of osteoclast markers, including TRACP (r = 0.784) and cathepsin K (r = 0.659), all with p <0.001.ConclusionsRabbits with type 1 diabetes experience an expansion of marrow adiposity, and this enhanced marrow adiposity is associated with increased osteoclast activity.